Internal Medicine Resident’s Knowledge and Attitudes towards Obstructive Sleep Apnoea in Riyadh City, Saudi Arabia: A Survey-based Cross-sectional Study - Mohammad A. Alhajery; Abdulwahed Abdulaziz Alotay; Eysa N. Alsolamy; Abdulrahman Mohammed Alanazi; Rayan A. Qutob; Yousef M. Alammari; Ismail S. Alateeq; Najd Mabrouk Alanazi; Abdulaziz M Aleidan; Fahad Awadh Alanazi; Tariq Radi Alanazi; Abdulaziz Abdulmajeed Alotay (Advances in Human Biology)
Introduction: Obstructive sleep apnoea (OSA) is a widespread yet underdiagnosed condition with significant health risks, including cardiovascular and metabolic issues. Factors such as obesity, age and gender heighten OSA risk. Internal medicine physicians’ limited OSA knowledge and screening delays diagnosis. This Saudi study assesses internal medicine residents’ OSA awareness to enhance care quality. Materials and Method: A cross-sectional survey-based study included internal medicine residents in Riyadh city. Participants were chosen using a convenience sampling technique. An online questionnaire was sent to each potential participant via E-mail or WhatsApp, including a previously validated Obstructive Sleep Apnoea Knowledge and Attitude questionnaire. Socio-demographic variables were analysed using descriptive statistics. A Chi-square test, independent sample t-test, analysis of variance and Spearman rank correlation were employed. A value of P < 0.05 was regarded as significant in statistical terms. Results: A total of 191 participants consented to fill out the questionnaire. The average knowledge score was 10.94 ± 3.15 for all participants (out of 18). Senior residents (3rd and 4th year residents) had a higher mean score scores (11.82 ± 2.77) than junior residents (1st and 2nd year residents) (10.47 ± 11.81). The overall attitude score was 13.81 ± 3.10. Senior residents showed a significantly higher total attitude score (14.53 ± 2.90) than juniors (13.43 ± 3.15), with P = 0.020. A positive correlation was observed between attitude and knowledge levels. Conclusion: These findings emphasise the critical significance of including OSA in the teaching curriculum for internal medicine residents to improve their knowledge and attitude. Furthermore, hands-on clinical experience is vital to increase the confidence level in OSA diagnosis and management, which will ultimately have a positive impact on the overall patient outcomes.